Father found strength to receive Posthumous Award for son - Nor Salwana, Mohammad Idris (2022)
PAYA BESAR, 6 November 2022 - As other parents were happy to celebrate their children’s graduation, Ab Razak Ahmad, 67 and Norhana Hanim Abdullah, 65, stayed strong to receive the Posthumous Award for their son on the second day of the 17th Universiti Malaysia Pahang (UMP) Convocation Ceremony today.